Neuroanatomical alterations in people with high and low cannabis dependence. (January 2020) - Lorenzetti, Valentina; Chye, Yann; Suo, Chao; Walterfang, Mark; Lubman, Dan I; Takagi, Michael; Whittle, Sarah; Verdejo-Garcia, Antonio; Cousijn, Janna; Pantelis, Christos; Seal, Marc; Fornito, Alex; et al.
Objectives: We aimed to investigate whether severity of cannabis dependence is associated with the neuroanatomy of key brain regions of the stress and reward brain circuits. Methods: To examine dependence-specific regional brain alterations, we compared the volumes of regions relevant to reward and stress, between high-dependence cannabis users (CD+, n  = 25), low-dependence cannabis users (CD−, n  = 20) and controls ( n  = 37). Results: Compared to CD− and/or controls, the CD+ group had lower cerebellar white matter and hippocampal volumes, and deflation of the right hippocampus head and tail. Conclusion: These findings provide initial support for neuroadaptations involving stress and reward circuits that are specific to high-dependence cannabis users.